The implementation of Halal food awareness among undergraduate students/ Faradewi Bee A Rahman ... [et al.] - A Rahman, Faradewi Bee; Osman, Suriati; Ismail, Faridah Hanim; Azman, Asma; Ahmad Termizi, Nursyazrina; Dahri, Siti Zarifah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study is to explore the inter-relationship between Halal attributes (religious belief, attitude, Halal certificate, and Halal logo) and Halal awareness among undergraduate students in the Faculty of Hotel and Management. The aims of this study are supported by the following objectives: (1) To investigate the Halal food awareness attributes among undergraduate students; (2) To examine the direct effect of Halal food awareness attributes among undergraduate students. Following the research, a survey was done to observe Halal awareness among undergraduate students. Conducted via Google form, the data collected 128 responses. Data were analyzed using SPSS version 26. The study findings primarily indicate religious belief, attitude, Halal certificate, and Halal logo give an impact on awareness.